STIM and Orai Mediated Regulation of Calcium Signaling in Age-Related Diseases - Collins, Helen E.; Zhang, Dingguo; Chatham, John C. (Frontiers in Aging, 2022)
Tight spatiotemporal regulation of intracellular Ca2+ plays a critical role in regulating diverse cellular functions including cell survival, metabolism, and transcriptions. As a result, eukaryotic cells have developed a wide variety of mechanisms for controlling Ca2+ influx and efflux across the plasma membrane as well as Ca2+ release and uptake from intracellular stores. The STIM and Orai protein families comprising of STIM1, STIM2, Orai1, Orai2, and Orai3, are evolutionarily highly conserved proteins that are core components of all mammalian Ca2+ signaling systems. STIM1 and Orai1 are considered key players in the regulation of Store Operated Calcium Entry (SOCE), where release of Ca2+ from intracellular stores such as the Endoplasmic/Sarcoplasmic reticulum (ER/SR) triggers Ca2+ influx across the plasma membrane. SOCE, which has been widely characterized in non-excitable cells, plays a central role in Ca2+-dependent transcriptional regulation. In addition to their role in Ca2+ signaling, STIM1 and Orai1 have been shown to contribute to the regulation of metabolism and mitochondrial function. STIM and Orai proteins are also subject to redox modifications, which influence their activities. Considering their ubiquitous expression there has been increasing interest in the roles of STIM and Orai proteins in excitable cells such as neurons and myocytes. While controversy remains as to the importance of SOCE in excitable cells, STIM1 and Orai1 are essential for cellular homeostasis and their disruption is linked to various diseases associated with aging such as cardiovascular disease and neurodegeneration. The recent identification of splice variants for most STIM and Orai isoforms while complicating our understanding of their function, may also provide insight into some of the current contradictions on their roles. Therefore, the goal of this review is to describe our current understanding of the molecular regulation of STIM and Orai proteins and their roles in normal physiology and diseases of aging, with a particular focus on heart disease and neurodegeneration.